Você está na página 1de 4

3 × 10 8 m

s

m rel =

m

1 v c 2

m v

c

( v c ) 2 = γ

m rel = γm

12, 5 m

1

= m 1 − v c 2 m → v → c → ( v c

1

s

γ =

1

1

1

v c 2 =

12,5

1

3×10 8 2

γ =

1

1 (0, 00000004) 2

γ =

1

1 0, 00000000000002

0, 00000000000002 0

1

γ =

1 0 = 1

m rel = m (v c)

vc γ = lim

lim

vc

1

1 v c 2

γ v c v = c

vc γ = lim

lim

vc

1

1

c

c

2

vc γ = lim

lim

vc

1

1 1

vc γ = lim

lim

vc

1

0

v c γ c v

v c c 0

vc lim γ =

vc m rel = lim

lim

vc γm

vc m rel = lim

lim

vc · m

lim

vc m rel =

E =

mc 2

1 v c 2

E = γmc 2

E = m rel c 2

vc E = lim

lim

vc m rel c 2

vc E = lim

lim

vc · c 2

vc lim E =

F = ma

F = m rel a

F

m rel

=

a

F rel F 0

m

lim

vc

F

m

rel

= lim

vc a

lim

vc

F

= lim

vc a

0 = lim

vc a